Management of bile ducts injuries in gastroenterology and hepatology teaching hospital - Al- Saidy, Mohammed Hussain; Hameed, Weesam Shaker; Rashid, Basher Abedallh (AL-Kindy College Medical Journal, 2014)
Background :The incidence of bile ducts injuries( BDI )has risen from) 0.1 to 0.2%( to) 0.4 to 0.6% ( between the era of open cholecystectomy( O C) and the age of laoaroscopic cholycystectomy( LC.) The aim of the study is to review the management and surgical outcome of the bile duct injuries in gastroenterology and hepatology teaching hospital .Methods: This study is Prospective, done in G.I.T hospital ,From January 2008 –to –February 2011, patients included in this study had prevouse history of cholecystectomy which followed by sign and symptoms of bile duct injures .Most patients have been reffered from other hospitals,supprting therapy were given to them and investigations performed to evaluate the the type of injureis ,minor injuries managed conservatively and by using ERCP while major injuries reconstructive surgery done in form of Roux en y bilioenteric anastomosis,All patients followed up for 8 -50 months by doing liver function tests ,abdominal US and MRCP for some patients .Assesment the out come of the patients using Treblanche grading to good,fair and poor Results: The total number of patients are 53 , female were 37 patients (70.5%) 16 patients (29%) were male.The range of age group from 18 -65 years.Average age is 29 years .Patient with minor BDI treated with drainage and ERCP, while 36 patients had major BDI treated by surgical reconstruction by elective manner using a technique Roux en Y (HJ). Follow up done for (8—50 months). (69.4%) have good result, (25%) got fair result and (5.5%) had poor results which mainly occur in E3 and E4 type injuriesConclusions: .If the diagnosis of BDI occurrence is delayed more than 24h , any attempt of primary reconstruction should be avoided and early referral of the patient to a tertiary care centre with experienced hepatobiliary surgeons and skilled interventional radiologists to assure optimal short-term and long-term outcome